Exploration of Enterprise Risk: An Analysis of Financial Leverage, Intangible Assets, and Earnings Management Practices - Erna Sari; Hisar Sirait; Rizqy Aziz Basuki; Ratih Nur Setyaningsih; Rahmat Ramli (Universitas Bina Sarana Informatika, 2025)
This research project aims to investigate the impact of financial leverage, intangible assets, and earnings management on corporate risk within the manufacturing sector. The principal objective is to comprehend the manner in which these variables interact and exert influence on the overall risk profile of companies within this pivotal economic sector. Quantitative research methodology, utilizing secondary data sourced from the Indonesia Stock Exchange. The data collection process entails the documentation of financial reports and pertinent metrics, thereby facilitating a comprehensive analysis of the relationships between the identified variables. The application of statistical analysis techniques allows for the assessment of the significance and strength of these relationships, thereby providing insights into the dynamics of corporate risk management. The findings demonstrate that elevated financial leverage is linked to augmented financial risk, as organizations with substantial debt burdens encounter heightened difficulties in fulfilling their obligations during economic downturns. Furthermore, the existence of intangible assets, while potentially advantageous for growth, also introduces an element of uncertainty that can have a detrimental impact on corporate risk. Furthermore, the findings indicate that earnings management practices can distort the accurate representation of a company's financial health, leading to misinformed decision-making by stakeholders. In conclusion, the research highlights the significance of comprehending the interrelationship between financial leverage, intangible assets, and earnings management in the context of corporate risk mitigation. The insights gained from this study can assist management in making informed strategic decisions, thereby enhancing the resilience and sustainability of manufacturing firms in the face of economic challenges.